Exploring knowledge, attitudes and practices towards COVID-19 amongst the residents in South Africa: a quick online survey - Wadhwani, Gyandas G.; Scott, Leanne; Nienhuis, Chantelle; Chella, Laura; Chadha, Aditi; Ferrucci, Loretta (International Journal Of Community Medicine And Public Health, 2021)
Background: The novel coronavirus (COVID-19) pandemic has spread rapidly inviting unprecedented measures globally. Citizen’s adherence to jurisdiction is affected by their knowledge, attitudes, and practices (KAP) towards the disease. Methods: A cross-sectional survey study among a convenient sample of the general public aged 18 years or more and resident in South Africa was conducted through a self-designed online KAP survey questionnaire during the first few weeks of the South African lockdown to assess the knowledge, attitudes and practices about COVID-19. A p value of <0.05 (two tailed) was taken to be statistically significant. Results: A total of 885 respondents completed the survey, majority of which were females who identified COVID-19 as a challenge to health and society and agreed with the strategy of lockdown for initial control of the spreading epidemic. In spite of the high knowledge scores of the population 31% of the respondents did not choose to wear a mask while leaving home. Also, a large number of respondents believed that early symptomatic treatment can prove useful to manage the infection. A statistically significant p value (<0.05) was obtained for the study variables in the statistical analysis, which showed that high knowledge scores were found to be associated with gender, categories of annual income and ethnicity. Conclusions: This survey shows that South African residents of a relatively high level of socioeconomic status, in particular women, have substantial knowledge, positive attitudes, but need to improve practices towards COVID-19 during the rapid rise phase of the COVID-19 outbreak.